2020
DOI: 10.3389/fpls.2020.01035
|View full text |Cite
|
Sign up to set email alerts
|

A Development-Associated Decrease in Osmotic Potential Contributes to Fruit Ripening Initiation in Strawberry (Fragaria ananassa)

Abstract: Fruit development and ripening are accompanied by a large increase in cellular soluble solid contents, which results in a significant decrease in osmotic potential (DOP). Here, we report that this development-associated DOP contributes to the initiation of ripening in strawberry ( Fragaria ananassa Duch., Benihoppe) fruit. We show that fruit water potential significantly decreases at the onset of ripening as a result of the DOP. Further analysis using nuclear magnetic resonance spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
(100 reference statements)
1
5
0
Order By: Relevance
“…However, little attention has been paid in the literature to the significance of the osmotic potential-associated changes in the regulation of fruit ripening. Such an effect was recently shown in a study by Jia et al [ 17 ] where a sharp decline in cellular osmotic potential coincided with the onset of strawberry fruit ripening. Moreover, by manipulating the changes in osmotic potential, the authors reported being able to modulate ripening.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, little attention has been paid in the literature to the significance of the osmotic potential-associated changes in the regulation of fruit ripening. Such an effect was recently shown in a study by Jia et al [ 17 ] where a sharp decline in cellular osmotic potential coincided with the onset of strawberry fruit ripening. Moreover, by manipulating the changes in osmotic potential, the authors reported being able to modulate ripening.…”
Section: Introductionsupporting
confidence: 56%
“…Given that fruit ripening is such an important part of the life cycle of many plants, it is not surprising that many studies have shown that the progression of fruit ripening is sensitive to environmental signals. For example, the progression of strawberry fruit ripening is extremely sensitive to illumination, temperature and water availability [ 17 , 83 ]. A minor elevation in temperature, (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cold stress is usually accompanied by dehydration and osmotic imbalance with time extending. Studies have certified that osmotin had a function in osmoregulation under stress and had adapted to low osmotic potential environments [ 14 , 24 , 56 ]. The expression levels of KoOsmotin were increased to substantial accumulation after 15 d under cold stress in among leaves, stems and roots.…”
Section: Discussionmentioning
confidence: 99%
“…N. benthamiana plants were used at 5.5 weeks old and the two youngest leaves chosen for at least six infiltration patches. Mature strawberry fruit (with fully developed seeds) were infiltrated at the initial reddening stage as described by (Jia et al, 2020) (Supplementary Figure 1A).…”
Section: Plant Materialsmentioning
confidence: 99%